LEGAL PROTECTION OF INTELLECTUAL PROPERTY RIGHTS OVER TRADITIONAL KNOWLEDGE ACQUISITION AGAINST ECONOMIC BENEFITS - Karlina Sofyarto (UNTAG Law Review, 2018)
Traditional knowledge is the result of innovation and creation of human beings both in terms of knowledge, art, and literature. Traditional knowledge can be utilized economically for the betterment and prosperity of society. The research method used is descriptive analytical with Juridical normative specification. Indonesia's Efforts in protecting intellectual property on traditional knowledge in Indonesia is the Indonesian government is preparing the Draft Law on Traditional Knowledge and Traditional Cultural Expression. Other Efforts that can be done is through the way of inventory or documentation of traditional knowledge in a region and can be done by publishing the traditional knowledge as Widely as possible. The underlying factors of traditional knowledge have not been optimally utilized as economic resources namely the lack of public knowledge about the protection of traditional knowledge and the cost of producing intellectual property is high enough